PENGARUH BAURAN KOMUNIKASI PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN BATIK DI RIVICHA PASAR KLEWER SOLO - Anggani, Mayawati Indah; Slamet, Giarti (Universitas Of Surakarta, 2023)
The purpose of this study was to determine the effect of the marketing communication mix variables on the purchasing decision of batik at Rivicha Klewer market, Solo. This research was conducted at Klewer market, Solo. The population in this purchase were all people who bought batik at Rivicha Pasar Klewer Solo totaling 42 respondents. The data taken was in the form of a questionnaire for the Marketing Communication Mix variable consisting of Advertising (X1), Sales Promotion (X2), Public Relations and Publications (X3), Personal Selling (X4), Direct Marketing (X5). The data analysis technique used is multiple linear regression. The results of the Multiple Linear Regression Test have shown: Y = -0.521+0.190 X_1+0.145 X_2+0.317 X_3+0.236 X_4+0.219 X_5+e. The t-test obtained results: Advertising (X1) obtained a significance coefficient of 0.190 with a t-count value of 2.076 with a probability value of 0.045 thus Advertising (X1) has a positive effect on Purchase Decision (Y). Sales Promotion (X2) obtains a significance coefficient of 0.145 with a t-count value of 2.111 with a probability value of 0.042 thus Sales Promotion (X2) has a positive effect on Purchase Decision (Y). Public Relations and Publications (X3) obtained a significance coefficient of 0.317 with a t-count value of 2.134 with a probability value of 0.040 thus Public Relations and Publications (X3) had a positive effect on Purchase Decision (Y).Personal Sales (X4) obtains a significance coefficient of 0.236 with a t-count value of 2.076 with a probability value of 0.045 thus Personal Sales (X4) has a positive effect on Purchase Decision (Y). Direct Marketing (X5) obtains a significance of 0.219 with a t-count value of 2.100 with a probability value of 0.043 thus Direct Marketing has a positive effect on Purchase Decision (Y). Based on the F test obtained F count 22,603 with a probability value of 0,000. Because this significance value is less than 0.05, this means that Advertising (X1), Sales Promotion (X2), Public Relations and Publications (X3), Personal Selling (X4), and Direct Marketing (X5) simultaneously or jointly have an influence significant to Purchase Decision (Y).